Facial Feminization Surgery: A Systematic Review of Perioperative Surgical Planning and Outcomes. Issue 3 (17th March 2022) - Tirrell, Abigail R.; Abu El Hawa, Areeg A.; Bekeny, Jenna C.; Chang, Brian L.; Del Corral, Gabriel
Abstract : Background: Facial feminization is a critical step in a transfeminine patient's surgical transition. However, the existing literature on the various types of feminization surgeries suffers from inadequate reporting on perioperative aspects of care, such as preoperative evaluation and postoperative outcomes. The aim of this study is to evaluate facial feminization surgery (FFS), preoperative planning, and patient reported outcomes after various types of procedures. Methods: An electronic database search of Ovid MEDLINE was completed according to PRISMA guidelines for articles pertaining to FFS. Study characteristics, operative information, and patient demographics were collected. Data concerning preoperative imaging, virtual simulation, postoperative complications, and patient-reported outcome measures (PROMs) were collected and analyzed for patterns. Results: A total of 22 papers representing 1302 patients were included for analysis. The most commonly discussed operations included upper face procedures, particularly of the forehead (17 studies, 77%). When discussed, preoperative planning for FFS included standard photography in 19 (86%) studies, advanced imaging, such as cephalometry or computed tomography, in 12 (55%) studies, and virtual simulation of surgical outcomes in four (18%) studies. Patient-centered outcomes, such as postoperative satisfaction, were described in 17 (77%) studies. Standardized PROMs were heterogenous across included studies with only 11 (50%) including at least one PROM. Conclusions: FFS is common, safe, and highly satisfying for transfeminine patients seeking surgical intervention for identity actualization. Future research concerning transgender care must evaluate advanced surgical planning and 3D simulation combined with more standardized assessment of PROMs to ensure high-quality analysis of patient satisfaction.